Species composition, bioecology and importance of earthworms in the Fergana Valley - Madumarov Sardar Ravshanjon O’g’li (Zien Journals, 2022)
The types of earthworms and their structure are explained. It was mentioned about the biological significance of the earthworm, what beneficial properties it has for the soil and plants.
Keywords: Biohumus; California earthworm; Nicodrilus caliginosus; Oxtolasium lacteum